2013
DOI: 10.1186/1475-2891-12-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a plant sterol, fish oil and B vitamin combination on cardiovascular risk factors in hypercholesterolemic children and adolescents: a pilot study

Abstract: BackgroundAssessment of cardiovascular disease (CVD) risk factors can predict clinical manifestations of atherosclerosis in adulthood. In this pilot study with hypercholesterolemic children and adolescents, we investigated the effects of a combination of plant sterols, fish oil and B vitamins on the levels of four independent risk factors for CVD; LDL-cholesterol, triacylglycerols, C-reactive protein and homocysteine.MethodsTwenty five participants (mean age 16 y, BMI 23 kg/m2) received daily for a period of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 32 publications
(35 reference statements)
1
50
0
1
Order By: Relevance
“…These results are very important because of the poor tools that physicians have when treating children diseases. Garaiova et al (2013) corroborate the evaluations of Guardamagna et al (2011) by outlining that the early administration of nutraceuticals in hypercholesterolaemic children could really improve their lipid levels.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…These results are very important because of the poor tools that physicians have when treating children diseases. Garaiova et al (2013) corroborate the evaluations of Guardamagna et al (2011) by outlining that the early administration of nutraceuticals in hypercholesterolaemic children could really improve their lipid levels.…”
supporting
confidence: 70%
“…As many studies (Casas-Agustench et al, 2012;Demonty et al, 2006;Garaiova et al, 2013;Gonç alves et al, 2006;Guardamagna et al, 2011;Maki et al, 2012;Pá rraga et al, 2011;Weingä rtner et al, 2009;Zhao et al, 2011) have already indicated, plant sterols are able to actively influence lipid profile. The mean LDL-cholesterol reduction after consumption of plant sterol-supplemented foods ranges from 5.9% to 10.4% (Casas-Agustench et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for analyzing of thiols (Cys, HCy and GSH) concentration in plasma by HPLC system were pre-treated according to Garaiova et al (2013). A mixture of 100 µl of plasma, 50 µl internal standards and 40 µl sodium borohydride was incubated for 30 minutes at 50°C to reduce and release protein-bound thiols, after which 100 µl perchloric acid was added to deproteination.…”
Section: Determination Of Thiol Samplesmentioning
confidence: 99%
“…Obtained serum was storaged at -80 °C until the analysis. Serum samples were pre-treated according to GARAIOVA et al (2013). Shortly, 40 µL of sodium borohydride (1 mol/L in 0.1 mol/L NaOH) was added to 100 μL of the serum, mixed and incubated at 50 °C for 30 min.…”
Section: Blood Collection and Sample Pretreatmentmentioning
confidence: 99%